The educational philosophies of Camilo Osias and Pedro T. Orata a comparative analysis - Halili, Adoracion Mamawi (Education quarterly.)
These educators, each in his own time had contributed and worked vigorously towards the development of our country in general. Osias has shown distinctive achievements as (1) a person (2) a professional (3) an educator (4) a politiciam and (5) an agent in promoting social change - more specifically for a dynamic Filipinism. He is always be remembered as a dynamic nationalist and a stout defender of academic freedom and civil liberties.